Dimensions of identity strength and organizational citizenship behavior (OCB) in establishing good university governance and performance of religious ideology-based higher educations. (21st March 2019) - , Munawir; Raharjo, Kusdi; Djalil, Muslim A.; Syahputra, Hendra; Muslim, Buhori; Adam, Muhammad
Abstract : Purpose: The purpose of this paper is to determine the effect of identity strength and organizational citizenship behavior (OCB) on good university governance and its impact on performance of religious ideology-based universities. Design/methodology/approach: The design of this study was an explanatory design. This study had a deductive theoretical direction; therefore, the core method was quantitative. The "import" strategy served as a complement to the main method. With the time horizon, the selection of research objects in religious ideology-based universities managed by foundations, where the funds management of universities are sourced from the people, is based on the consideration that at present, the identity strength that is inherent in a higher education is funded by the people, as well as OCB is reflected in the behavior of people in the organization so that it has an impact on good university governance and performance, as described in the background at the beginning of this paper. Findings: The successful the OCB is, the successful the good university governance and performance will be. The successful the good university governance is, the successful the university performance will be. In the mediation effect testing, it was found that good university governance had a significant mediation effect on relationship between OCB and university performance. It shows that good university governance strengthens the relationship between OCB and university performance. Originality/value: Originality in this study is testing the mediating effect of good university governance that collaborates with OCB and performance variables, which are carried out at religious ideology-based universities in Indonesia that have different characteristics from universities in other regions. Originality in this study is as follows: good university governance and performance have been studied in a lot of previous research, but in this study, the focus of research is on religious ideology-based higher educations, where it is known that religious ideology-based universities are full with ideological values that become brands, if ideological identity used as one of the formers of good university governance and performance, it is expected that the accountability and performance of higher education will be better.